Shifting Chinese diets for a win-win of health and the environment - Sheng, Fangfang; Gao, Haixiu; Fan, Shenggen; Chen, Kevin Z.; Zhang, Yumei; Zhu, Chen; Zhao, Qiran (2021)
With rapid improvements in agricultural productivity and residents’ income, China has made remarkable advances in reducing hunger and malnutrition, as well as quality improvements in residents’ diets, witnessed by the progressively increasing consumption of fruits, eggs, aquatic products, and milk. However, new health and environmental challenges also arise alongside China’s dietary transition. Specifically, overweight and obesity have become increasingly prominent, and the incidence of diet-related chronic diseases has been on the rise. Among all these trends, the significant increase in meat consumption not only led to nutrition and health challenges, but also imposed intense pressure on resources and the environment. There are significant gaps between the current diet of Chinese residents and the recommended diets of the Chinese Dietary Guidelines and the EATLancet Commission. The current Chinese diet is mainly composed of grains, dominated by refined rice and noodles, insufficient coarse food grains, excessive meat, and insufficient consumption of whole grains, fruits, legumes, and milk. Incidence and mortality from diet-related chronic diseases in China would be significantly reduced if the “healthy diet” recommendations of the Chinese Dietary Guidelines, EAT-Lancet, Mediterranean and flexitarian (or low meat) diets were adopted. Deaths in China would be reduced by 1.15 million by 2030 if the population were following the Chinese Dietary Guidelines, or 1.8 million by shifting to the EAT-Lancet diet. At the same time, such a shift would significantly lower greenhouse gas emissions. Simulation results show that greenhouse gas emissions from agricultural activities would be reduced by 146-202 million metric tons if residents adopted one of the healthy diets, and by 60-116 million metric tons compared with food consumption at the 2020 level. The flexitarian diet would reduce greenhouse gas emissions the most.